Strategy of increase of competitiveness of the Russian automotive industry - A. Z. Gusov; S. V. Buravov (Путеводитель предпринимателя)
In the article the analysis of major factors and the directions of increase of competitiveness of the Russian automotive industry in the conditions of formation of modern innovative economy.